Evaluation of the Stunting Program at the Margototo Health Center, Lampung East District - Ida Rahayu; Syamsulhuda Budi Musthofa; Apoina Kartini (Postgraduate, University of Mataram, 2023)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the first 1,000 days of life. Stunting can affect brain growth and development. Children with stunting have a greater risk of suffering from chronic diseases in adulthood. This study aims to analyze the evaluation of the implementation of the stunting program at the Margototo Health Center, East Lampung Regency. This research is a program evaluation research using a mixed method (Mix Method) with a sequential explanatory design where quantitative data analysis is carried out at the initial stage, then qualitative data analysis is carried out. The program evaluation method uses the context-input-process-product (CIPP) evaluation model. Results study shows that in terms of context, the stunting program has been implemented according to the planned objectives and is right on target. In the input aspect, namely the lack of human resources in assisting, the lack of a budget that supports program implementation. In the process aspect of program implementation, there were no significant obstacles, and the process of implementing the stunting program went according to plan. In the product/output aspect, the stunting program has reached the expected target indicators, and recording and reporting have been going well. And the results of the implementation of the stunting program are shown by the results of mothers' knowledge about stunting and the attitudes of mothers who have stunted toddlers towards stunting events.